Pengaruh Capital Intensity Dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak Dengan Inventory Intensity Sebagai Variabel Moderasi - Ester Indah Sari Telaumbanua; Adi Supriadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of Capital intensity and Sales Growth on Tax Avoidance with Inventory Intensity as a moderating variable. The research was conducted on Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The sampling technique used was purposive sampling, resulting in 13 companies as research samples. The data used in this study are secondary data in the form of companies’ annual financial statements. The independent variables in this study are Capital intensity (X1) and Sales Growth (X2), the dependent variable is Tax Avoidance (Y), and the moderating variable is Inventory Intensity (Z). Panel data regression analysis was employed using EViews version 12, and the best estimation model selected was the Fixed Effect Model (FEM). The results show that simultaneously Capital intensity and Sales Growth have a significant effect on Tax Avoidance. Partially, Capital intensity has no effect on Tax Avoidance, while Sales Growth has a significant effect on Tax Avoidance. Furthermore, the moderation test indicates that Inventory Intensity does not moderate the relationship between Capital intensity and Tax Avoidance, but it is able to moderate the relationship between Sales Growth and Tax Avoidance.